2018
DOI: 10.1128/mcb.00197-18
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a Novel Enhancer/Chromatin Opening Element Associated with High-Level γ-Globin Gene Expression

Abstract: The organization of the five β-type globin genes on chromosome 11 reflects the timing of expression during erythroid cell development, with the embryonic ε-globin gene being located at the 5′ end, followed by the two fetal γ-globin genes, and with the adult β- and δ-globin genes being located at the 3′ end. Here, we functionally characterized a DNase I-hypersensitive site (HS) located 4 kb upstream of the Gγ-globin gene (HBG-4kb HS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…These results are of interest because they support the hypothesis that LYAR is a major player in γ-globin gene regulation in β-thalassemia. Recently published studies have demonstrated that several transcription factors interact with several elements of the γ-globin gene promoter to control γ-globin gene expression in erythroid cells [9][10][11][12]. For instance, several of them (e.g., BCL11A) are (as LYAR) strong repressors of γ-globin gene transcription [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are of interest because they support the hypothesis that LYAR is a major player in γ-globin gene regulation in β-thalassemia. Recently published studies have demonstrated that several transcription factors interact with several elements of the γ-globin gene promoter to control γ-globin gene expression in erythroid cells [9][10][11][12]. For instance, several of them (e.g., BCL11A) are (as LYAR) strong repressors of γ-globin gene transcription [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several transcription factors are known that interact with elements of the γ-globin gene promoter, thereby controlling γ-globin gene expression in erythroid cells [10][11][12][13][14][15][16][17][18]. Several of them (e.g., MYB and BCL11A) are strong repressors of γ-globin gene transcription [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, recruiting BAF to the enhancer regions did not significantly increase the expression of globin genes HBG1, HBE and HBB in either cell line (Supplemental figure 2A-B). In addition, further ChIP-sequencing analysis of Histone 3 lysine 4 monomethylation (H3K4me1) and Histone 3 lysine 27 acetylation (H3K27Ac), coupled with ATAC-sequencing and genomic perturbation studies have identified a locus within the BGLT3 gene and a locus 4-kilo base pairs upstream of the HBG promoter (HBG-4KBP) to be novel enhancers that regulate HBG1 expression [44][45][46] . We therefore designed sgRNAs to recruit BAF to these novel loci.…”
Section: Recruitment Of Baf To the Hbg1 Promoter Induces Gene And Pro...mentioning
confidence: 99%
“…Many datasets exploring erythroid and other hematopoietic cells have been uniformly processed and made publically available in the framework of the VISION project [13], which comprises over 200,000 candidate CREs, including almost all experimentally verified erythroid CREs. This and other databases (for example, the ENCODE project) are an extremely valuable resource for the discovery of new CREs, as exemplified by a newly found functional enhancer upstream of the Gg-globin gene [22].…”
Section: The Erythroid Chromatin Landscapementioning
confidence: 99%